Voters Apathy During Students’ Union Elections: Implication for Social Studies and Political Science Students - Soluade, Zabur Olayiwola; Moliki, Ahmed Olawale; Balogun, Olukunle Olagunju; Adebajo, Yesiru Adebola; Oyekanmi, Abdullahi Abiodun (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The study assesses the implications of voter apathy during students’ union elections on Social Studies and Political Science Students. The study assesses the levels of student voter apathy; examine reasons for voter apathy and influence of Social Studies and Political Science on students’ political participation in the student union election. Three (3) research questions were raised and answered in the study. The study adopted descriptive research design. The target population of the study consists of all the Social Studies and Political Science of Tai Solarin University of Education, Ijagun, Ogun State. Six hundred and twenty (620) students were selected for the study, using purposive and stratified random sampling techniques. A self-designed questionnaire tagged “Students and Voting Apathy Questionnaire” (SVAQ) was used to obtain information from the respondents. The data were analysed using descriptive analysis of frequency, percentage mean and standard deviation. The findings show that voter apathy among social studies and political science students during students’ union elections is unabated; popular students’ inclination that voting during a students’ union election is a voluntary exercise; students have negative perceptions about candidates fulfilling their electoral promises; and Social Studies and Political Science have an influence on students’ active participation and voting during student unions’ election. The study recommended that voting during students’ union election should be made compulsory for the students of Social Studies and Political Science and that management of higher institutions of learning must adopt e-voting to de-radicalise students’ elections and enhance active participation of students’ confidence of students in voting during student union elections.